Modified lithium battery precursor and preparation method thereof, positive electrode material, and lithium ion battery
By using Cu-doped ZrTaON and TiO2 composite material to coat the nickel-cobalt-manganese hydroxide lithium battery precursor, the limitations of traditional lithium battery positive electrode materials in terms of high temperature performance and long cycle life are solved, and the performance of lithium-ion batteries is improved.
Patent Information
- Application Number
- CN202411901678.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
AI Technical Summary
Traditional lithium battery positive electrode materials have limitations in high temperature performance and long cycle life, and cannot meet the needs of improving lithium-ion battery performance.
A composite material doped with Cu-doped ZrTaON and TiO2 is coated with nickel-cobalt-manganese hydroxide lithium battery precursor, and a modified lithium battery precursor is formed by heat treatment to prepare a positive electrode material.
It effectively improves the electrochemical performance and structural stability of the cathode material, and improves the electrical performance and cycle life of lithium-ion batteries.
Smart Images

Figure CN119750670A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery positive electrode materials, and in particular relates to a lithium ion battery precursor and a preparation method thereof, a positive electrode material and a preparation method thereof. Background Art
[0002] In lithium-ion batteries, the key to improving performance lies in the development of new cathode materials. Although traditional lithium battery cathode materials, such as LiCoO2 and LiFePO4, have a place in applications, they show limitations in high temperature performance and long cycle life. In contrast, ternary materials (such as nickel cobalt manganese oxide) as cathode materials have received widespread attention due to their excellent energy density and cycle stability. Therefore, the exploration and development of new cathode materials has become an important way to break through the limitations of traditional materials and further improve the performance of lithium-ion batteries.
[0003] In lithium-ion batteries, the performance of cathode materials is crucial. Although traditional lithium battery cathode materials have good electrochemical properties, they are limited in energy density and cycle stability. Currently, coating and doping are commonly used for modification. Summary of the invention
[0004] In response to the above technical problems, the present application provides a modified lithium battery precursor and a preparation method thereof, a positive electrode material and a lithium ion battery.
[0005] To achieve the above objectives, this application proposes the following technical solutions: In a first aspect, a modified lithium battery precursor is provided, including a lithium battery precursor and a coating layer located on at least a portion of the surface of the lithium battery precursor, wherein the lithium battery precursor is nickel cobalt manganese hydroxide, and the coating layer is composed of a composite material of Cu-doped ZrTaON and TiO2.
[0006] Furthermore, the chemical formula of the nickel-cobalt-manganese hydroxide is Ni x Co y Mn z (OH)2, where 0.6≤x<1, 0≤y≤0.2, 0<z≤0.3, x+y+z=1.
[0007] Furthermore, the mass ratio of the coating layer to the lithium battery precursor is 0.005-0.05:1.
[0008] In the coating layer, the molar ratio of Cu-doped ZrTaON to TiO2 is 1:0.1-2, preferably 1:0.2-1.5.
[0009] In the Cu-doped ZrTaON, the molar ratio of Cu to Zr is 0.005-0.1:1.
[0010] In a second aspect, a method for preparing the aforementioned modified lithium battery precursor is provided, comprising: S1. preparing Cu-doped ZrTaON material; S2, mixing Cu-doped ZrTaON and TiO2 and ball-milling to obtain a mixed powder, and heat-treating the mixed powder to obtain a composite material of Cu-doped ZrTaON and TiO2; S3, mixing nickel-cobalt-manganese hydroxide with the composite material, and then performing heat treatment to obtain a modified lithium battery precursor.
[0011] In a third aspect, a positive electrode material is provided, which is obtained by mixing the aforementioned modified lithium battery precursor with a lithium source and then sintering.
[0012] In a fourth aspect, a lithium-ion battery is provided, comprising the aforementioned positive electrode material.
[0013] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: The use of Cu-doped ZrTaON material and TiO2 composite materials to coat and modify lithium battery precursors can effectively improve the electrochemical properties and structural stability of the positive electrode material, thereby improving the electrical performance and cycle life of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 This is the XRD pattern of the product prepared in step S1 of Example 1. DETAILED DESCRIPTION
[0016] The present invention provides a modified lithium battery precursor, comprising a lithium battery precursor and a coating layer located on at least a portion of the surface of the lithium battery precursor, wherein the lithium battery precursor is nickel cobalt manganese hydroxide, and the coating layer is a composite material of Cu-doped ZrTaON and TiO2.
[0017] Compared with its single oxide (such as ZrO2 and Ta2O5), Cu-doped ZrTaON not only has higher conductivity and good chemical stability, but also can maintain excellent electrochemical performance in high temperature environment; the present invention can effectively improve the conductivity of the material and enhance the structural stability by Cu-doping ZrTaON. Therefore, by using Cu-doped ZrTaON to coat the modified lithium battery precursor, the electrical properties and structural stability of the positive electrode material can be effectively improved; and by compounding TiO2 in the coating layer, the electrode can improve the anti-decomposition and anti-volume expansion ability during repeated charge and discharge by improving the interface stability of the positive electrode material, inhibiting side reactions, protecting the structure, etc., thereby extending the cycle life of the battery.
[0018] In some preferred embodiments, the chemical formula of the nickel-cobalt-manganese hydroxide is Ni x Co y Mn z (OH)2, where 0.6≤x<1, 0≤y≤0.2, 0<z≤0.3, x+y+z =1.
[0019] In some preferred embodiments, the mass ratio of the coating layer to the lithium battery precursor is 0.005-0.05:1, for example, 0.005:1, 0.01:1, 0.015:1, 0.02:1, 0.025:1, 0.03:1, 0.035:1, 0.04:1, 0.045:1, 0.05:1, etc.
[0020] In some preferred embodiments, in the coating layer, the mass ratio of Cu-doped ZrTaON to TiO2 is 1:0.1~2, preferably 1:0.2~1, for example, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, etc.
[0021] In some preferred embodiments, in the Cu-doped ZrTaON, the molar ratio of Cu to Zr is 0.005-0.1:1, for example, 0.005:1, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1, etc.
[0022] The present invention also provides a method for preparing the aforementioned modified lithium battery precursor, comprising: S1. preparing Cu-doped ZrTaON material; S2, mixing Cu-doped ZrTaON and TiO2 and ball-milling to obtain a mixed powder, and heat-treating the mixed powder to obtain a composite material of Cu-doped ZrTaON and TiO2; S3, mixing nickel-cobalt-manganese hydroxide with the composite material, and then performing heat treatment to obtain a modified lithium battery precursor.
[0023] In some preferred embodiments, in step S1, the preparation of the Cu-doped ZrTaON material comprises: preparing the ZrTaON material; mixing the ZrTaON material with a copper source, and calcining the mixture in a nitrogen atmosphere to obtain the Cu-doped ZrTaON material.
[0024] In some embodiments, the copper source is one or more of copper oxide, copper sulfate, copper acetate, copper carbonate, and copper hydroxide.
[0025] In some preferred embodiments, the calcination temperature is 600-1000°C, more preferably 650-900°C, for example 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, etc.; the calcination time is 1-5h, for example 1h, 2h, 3h, 4h, 5h, etc.
[0026] In some preferred embodiments, the preparation of the ZrTaON material includes: dissolving zirconium chloride and potassium heptafluorotantalate in ammonia water according to a stoichiometric ratio, heating the reaction under a nitrogen atmosphere, washing, solid-liquid separation and drying the obtained product, and then sintering to obtain ZrTaON powder.
[0027] The nitrogen atmosphere can be achieved by introducing nitrogen into the reaction container.
[0028] The TiO2 can be commercially available or synthesized, and the synthesis method can be prepared by conventional methods. The use of newly synthesized titanium dioxide is beneficial to improving the surface activity and thus improving the composite effect. The preparation method of TiO2 can be achieved by hydrolysis, for example, including: dissolving an organic titanium source such as tetrabutyl titanate in a solvent, hydrolyzing to obtain titanium dioxide precipitate, and obtaining the target TiO2 through solid-liquid separation, washing and drying.
[0029] In some preferred embodiments, the temperature of the heating reaction is 50-80°C.
[0030] In some preferred embodiments, the sintering temperature is 800-1000°C, for example, 800°C, 850°C, 900°C, 950°C, 1000°C, etc.; the sintering time is 3-5h, for example, 3h, 3.5h, 4h, 4.5h, 5h, etc.
[0031] In some preferred embodiments, in step S2, the temperature of the heat treatment is 200-500°C, preferably 250-450°C, for example, 250°C, 300°C, 350°C, 400°C, 450°C, etc.; the time of the heat treatment is 1-6h, for example, 1h, 2h, 3h, 4h, 5h, 6h, etc.
[0032] In some preferred embodiments, in step S3, the temperature of the heat treatment is 200-400°C, for example, 200°C, 250°C, 300°C, 350°C, 400°C, etc.; the time of the heat treatment is 1-4h, for example, 1h, 2h, 3h, 4h, etc.
[0033] The present invention provides a positive electrode material, which is obtained by mixing the aforementioned modified lithium battery precursor with a lithium source and then sintering.
[0034] The present invention also provides a lithium ion battery, comprising the above-mentioned positive electrode material.
[0035] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.
[0036] Example 1 Step S1, preparation of ZrTaON: First, prepare 0.1 mol zirconium chloride (ZrCl4) and 0.1 mol potassium heptafluorotantalate (K2TaF7), dissolve them in 100 mL of 28 wt% ammonia water, and then heat to 60°C and stir to react. During the mixing process, nitrogen is introduced at a flow rate of 50 mL / min to ensure the protection of the reaction atmosphere and avoid oxidation. After the reaction, the obtained precipitate is washed with deionized water 3 times to remove excess ions, filtered and dried, and the obtained dry product is sintered in a nitrogen atmosphere at 900°C for 4 hours to finally obtain ZrTaON powder, whose XRD pattern is as shown below: Figure 1 shown.
[0037] Step S2, synthesis of Cu-doped ZrTaON: copper oxide (CuO) was added to the obtained ZrTaON powder, and the mixture was mixed at a molar ratio of ZrTaON to CuO of 100:5, and the mixture was sintered in a nitrogen atmosphere at 700° C. for 2 hours to obtain a Cu-doped ZrTaON composite material.
[0038] Step S3, preparation of TiO2: 10 mL of tetrabutyl titanate (Ti(OC4H9)4) was dissolved in 20 mL of isopropanol, followed by the addition of 50 mL of deionized water, and the pH was adjusted to 2 with 2M HNO3. The hydrolysis reaction was carried out at 80°C for 12 hours to obtain a TiO2 precipitate. After filtering and washing, the precipitate was dried at 100°C for 12 hours to obtain a TiO2 powder.
[0039] Step S4, composite of Cu-doped ZrTaON and TiO2: Cu-doped ZrTaON and TiO2 powder were mixed in a molar ratio of 1:1, ball-milled at 300 rpm for 6 hours to ensure uniform distribution, and then heat-treated at 400° C. for 3 hours to form a composite material of Cu-doped ZrTaON and TiO2.
[0040] Step S5: Cu-doped ZrTaON and TiO2 composite coating precursor Composite materials of Cu-doped ZrTaON and TiO2 and ternary precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 was mixed at a mass ratio of 0.01:1 and pretreated at 250°C for 4 hours to promote the bonding of the composite and the precursor. After sintering, the composite was cooled to room temperature to obtain a composite-coated precursor.
[0041] Step S6: Preparation of positive electrode material from the modified precursor The modified precursor and lithium hydroxide are reacted according to the precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and Li contained in lithium hydroxide are mixed in a molar ratio of 1:1.05, and sintered at 850°C in an air atmosphere for 22 hours to obtain a Cu-doped ZrTaON and TiO2 composite coated modified positive electrode material.
[0042] Comparative Example 1: Step S1, preparation of ZrTaON: prepare 0.1 mol zirconium chloride (ZrCl4) and 0.1 mol potassium heptafluorotantalate (K2TaF7), dissolve them in 100 mL of 28 wt% ammonia water and mix them. During the mixing process, nitrogen is introduced at a flow rate of 50 mL / min to promote the formation of ZrTaON. After the reaction, the precipitate is washed with deionized water for 3 times, and the product is sintered in a nitrogen atmosphere at 900°C for 4 hours after filtering to obtain ZrTaON powder.
[0043] Step S2, synthesis of Cu-doped ZrTaON: copper oxide (CuO) was added to the obtained ZrTaON powder, and the mixture was mixed at a molar ratio of ZrTaON to CuO of 100:5, and the mixture was sintered in a nitrogen atmosphere at 700° C. for 2 hours to uniformly dope the Cu element into the ZrTaON, thereby obtaining a Cu-doped ZrTaON material.
[0044] Step S3: Cu-doped ZrTaON coated precursor Cu-doped ZrTaON material and ternary precursor Ni 0.9 Co0.05 Mn 0.05 (OH)2 was mixed at a mass ratio of 0.01:1 and pretreated at 250°C for 4 hours to promote the bonding of the Cu-doped ZrTaON material with the precursor. After sintering, it was cooled to room temperature to obtain a Cu-doped ZrTaON-coated precursor.
[0045] Step S4: Preparation of positive electrode material from modified precursor The modified precursor and lithium hydroxide are reacted according to the precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and Li contained in lithium hydroxide were mixed in a molar ratio of 1:1.05, and sintered at 850°C in an air atmosphere for 22 hours to obtain a Cu-doped ZrTaON-coated modified positive electrode material.
[0046] Comparative Example 2: Step S1, preparation of ZrTaON: prepare 0.1 mol zirconium chloride (ZrCl4) and 0.1 mol potassium heptafluorotantalate (K2TaF7), dissolve in 100 mL of 28 wt% ammonia water and mix. During the mixing process, nitrogen is introduced at a flow rate of 50 mL / min to promote the formation of ZrTaON. After the reaction, the precipitate is washed with deionized water for 3 times, and the product is sintered in a nitrogen atmosphere at 900°C for 4 hours after filtering to obtain ZrTaON powder.
[0047] Step S2: ZrTaON coating precursor ZrTaON powder and ternary precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 was mixed at a mass ratio of 0.01:1 and pretreated at 250°C for 4 hours to promote the bonding of the ZrTaON material with the precursor. After sintering, the precursor was cooled to room temperature to obtain a ZrTaON-coated precursor.
[0048] Step S3: Preparation of positive electrode material from modified precursor The modified precursor and lithium hydroxide are reacted according to the precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and Li contained in lithium hydroxide were mixed in a molar ratio of 1:1.05, and sintered at 850°C in an air atmosphere for 22 hours to obtain a ZrTaON-coated modified positive electrode material.
[0049] Comparative Example 3: Step S1, preparation of ZrTaON: prepare 0.1 mol zirconium chloride (ZrCl4) and 0.1 mol potassium heptafluorotantalate (K2TaF7), dissolve them in 100 mL of 28 wt% ammonia water and mix them. During the mixing process, nitrogen is introduced at a flow rate of 50 mL / min to promote the formation of ZrTaON. After the reaction, the precipitate is washed with deionized water for 3 times, and after filtering, the product is sintered in a nitrogen atmosphere at 900°C for 4 hours to obtain ZrTaON powder.
[0050] Step S2, preparation of TiO2: 10 mL of tetrabutyl titanate (Ti(OC4H9)4) was dissolved in 20 mL of isopropanol, followed by addition of 50 mL of deionized water, and the pH was adjusted to 2 with 2M HNO3. The hydrolysis reaction was carried out at 80°C for 12 hours to obtain TiO2 precipitate. After filtering and washing, the precipitate was dried at 100°C for 12 hours to obtain TiO2 powder.
[0051] Step S3, composite of ZrTaON and TiO2: ZrTaON and TiO2 powders were mixed at a molar ratio of 1:1. The mixture was ball-milled at a speed of 300 rpm for 6 hours to ensure uniform distribution. Thereafter, the mixture was heat-treated at 400° C. for 3 hours to form a composite material of ZrTaON and TiO2.
[0052] Step S4: ZrTaON and TiO2 composite coating precursor The composite material and the ternary precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 was mixed in a mass ratio of 0.01:1 and pretreated at 250°C for 4 hours to promote the bonding of the composite material and the precursor. After sintering, the composite material was cooled to room temperature to obtain a composite-coated precursor.
[0053] Step S5: Preparation of positive electrode material from the modified precursor The modified precursor and lithium hydroxide are reacted according to the precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and Li contained in lithium hydroxide are mixed in a molar ratio of 1:1.05, and sintered at 850°C in an air atmosphere for 22 hours to obtain a positive electrode material coated and modified by a ZrTaON and TiO2 composite material.
[0054] Comparative Example 4: Step S1, preparation of TiO2: 10 mL of tetrabutyl titanate (Ti(OC4H9)4) was dissolved in 20 mL of isopropanol, followed by addition of 50 mL of deionized water, and the pH was adjusted to 2 with 2M HNO3. The hydrolysis reaction was carried out at 80°C for 12 hours to obtain TiO2 precipitate. After filtering and washing, the precipitate was dried at 100°C for 12 hours to obtain TiO2 powder.
[0055] Step S2: TiO2 coating precursor TiO2 and ternary precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 was mixed at a mass ratio of 0.01:1 and pretreated at 250°C for 4 hours to promote the bonding of TiO2 and the precursor. After sintering, it was cooled to room temperature to obtain a TiO2-coated modified precursor.
[0056] Step S4: Preparation of positive electrode material from modified precursor The modified precursor and lithium hydroxide are reacted according to the precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and Li contained in lithium hydroxide are mixed in a molar ratio of 1:1.05, and sintered at 850°C in an air atmosphere for 22 hours to obtain the corresponding TiO2-coated modified positive electrode material.
[0057] Comparative Example 5 The precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and lithium hydroxide were mixed at a molar ratio of 1:1.05 between the precursor and the Li contained in the lithium hydroxide, and sintered at 850°C in an air atmosphere for 22 hours to obtain a positive electrode material.
[0058] Example 2 Step S1, preparation of ZrTaON: first prepare 0.1 mol zirconium chloride (ZrCl4) and 0.1 mol potassium heptafluorotantalate (K2TaF7), dissolve them in 100 mL of 28 wt% ammonia water, and then heat to 50°C and stir to react. During the mixing process, nitrogen is introduced at a flow rate of 50 mL / min to ensure the protection of the reaction atmosphere and avoid oxidation. After the reaction, the precipitate is washed with deionized water 3 times to remove excess ions, filtered and dried, and the obtained dry product is sintered in a nitrogen atmosphere at 900°C for 4 hours to finally obtain ZrTaON powder.
[0059] Step S2, synthesis of Cu-doped ZrTaON: copper oxide (CuO) was added to the obtained ZrTaON powder, and the mixture was mixed at a molar ratio of ZrTaON to CuO of 100:1, and the mixture was sintered in a nitrogen atmosphere at 750° C. for 2 hours to obtain a Cu-doped ZrTaON composite material.
[0060] Step S3, preparation of TiO2: 10 mL of tetrabutyl titanate (Ti(OC4H9)4) was dissolved in 20 mL of isopropanol, followed by the addition of 50 mL of deionized water, and the pH was adjusted to 2 with 2M HNO3. The hydrolysis reaction was carried out at 80°C for 12 hours to obtain a TiO2 precipitate. After filtering and washing, the precipitate was dried at 100°C for 12 hours to obtain a TiO2 powder.
[0061] Step S4, composite of Cu-doped ZrTaON and TiO2: Cu-doped ZrTaON and TiO2 powder were mixed in a molar ratio of 1:1, ball-milled at 300 rpm for 6 hours to ensure uniform distribution, and then heat-treated at 300° C. for 4 hours to form a composite material of Cu-doped ZrTaON and TiO2.
[0062] Step S5: Cu-doped ZrTaON and TiO2 composite coating precursor Composite materials of Cu-doped ZrTaON and TiO2 and ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed at a mass ratio of 0.01:1 and pretreated at 300°C for 3 hours to promote the bonding of the composite and the precursor. After sintering, the composite was cooled to room temperature to obtain a composite-coated precursor.
[0063] Step S6: Preparation of positive electrode material from the modified precursor The modified precursor and lithium hydroxide are reacted according to the precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and Li contained in lithium hydroxide are mixed in a molar ratio of 1:1.05, and sintered at 850°C in an air atmosphere for 22 hours to obtain a Cu-doped ZrTaON and TiO2 composite coated modified positive electrode material.
[0064] Example 3 Step S1, preparation of ZrTaON: first prepare 0.1 mol zirconium chloride (ZrCl4) and 0.1 mol potassium heptafluorotantalate (K2TaF7), dissolve them in 100 mL of 28 wt% ammonia water, and then heat to 80°C and stir to react. During the mixing process, nitrogen is introduced at a flow rate of 50 mL / min to ensure the protection of the reaction atmosphere and avoid oxidation. After the reaction, the precipitate is washed with deionized water 3 times to remove excess ions, filtered and dried, and the obtained dry product is sintered in a nitrogen atmosphere at 850°C for 4 hours to finally obtain ZrTaON powder.
[0065] Step S2, synthesis of Cu-doped ZrTaON: copper oxide (CuO) was added to the obtained ZrTaON powder, and the mixture was mixed at a molar ratio of ZrTaON to CuO of 100:3, and the mixture was sintered in a nitrogen atmosphere at 700° C. for 2 hours to uniformly dope the Cu element into the ZrTaON, thereby obtaining a Cu-doped ZrTaON composite material.
[0066] Step S3, preparation of TiO2: 10 mL of tetrabutyl titanate (Ti(OC4H9)4) was dissolved in 20 mL of isopropanol, followed by the addition of 50 mL of deionized water, and the pH was adjusted to 2 with 2M HNO3. The hydrolysis reaction was carried out at 80°C for 12 hours to obtain a TiO2 precipitate. After filtering and washing, the precipitate was dried at 100°C for 12 hours to obtain a TiO2 powder.
[0067] Step S4, composite of Cu-doped ZrTaON and TiO2: Cu-doped ZrTaON and TiO2 powder were mixed in a molar ratio of 1:1, ball-milled at 300 rpm for 6 hours to ensure uniform distribution, and then heat-treated at 400° C. for 3 hours to form a composite material of Cu-doped ZrTaON and TiO2.
[0068] Step S5: Cu-doped ZrTaON and TiO2 composite coating precursor Composite materials of Cu-doped ZrTaON and TiO2 and ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed at a mass ratio of 0.01:1 and pretreated at 250°C for 4 hours to promote the bonding of the composite and the precursor. After sintering, the composite was cooled to room temperature to obtain a composite-coated precursor.
[0069] Step S6: Preparation of positive electrode material from the modified precursor The modified precursor and lithium hydroxide are reacted according to the precursor Ni 0.8 Co 0.1Mn 0.1 (OH)2 and Li contained in lithium hydroxide are mixed in a molar ratio of 1:1.05, and sintered at 850°C in an air atmosphere for 22 hours to obtain a Cu-doped ZrTaON and TiO2 composite coated modified positive electrode material.
[0070] Example 4 Step S1, preparation of ZrTaON: first prepare 0.1 mol zirconium chloride (ZrCl4) and 0.1 mol potassium heptafluorotantalate (K2TaF7), dissolve them in 100 mL of 28 wt% ammonia water, and then heat to 60°C and stir to react. During the mixing process, nitrogen is introduced at a flow rate of 50 mL / min to ensure the protection of the reaction atmosphere and avoid oxidation. After the reaction, the precipitate is washed with deionized water 3 times to remove excess ions, filtered and dried, and the obtained dry product is sintered in a nitrogen atmosphere at 1000°C for 4 hours to finally obtain ZrTaON powder.
[0071] Step S2, synthesis of Cu-doped ZrTaON: copper oxide (CuO) was added to the obtained ZrTaON powder, and the mixture was mixed at a molar ratio of ZrTaON to CuO of 100:5, and the mixture was sintered in a nitrogen atmosphere at 700° C. for 2 hours to uniformly dope the Cu element into the ZrTaON, thereby obtaining a Cu-doped ZrTaON composite material.
[0072] Step S3, preparation of TiO2: 10 mL of tetrabutyl titanate (Ti(OC4H9)4) was dissolved in 20 mL of isopropanol, followed by the addition of 50 mL of deionized water, and the pH was adjusted to 2 with 2M HNO3. The hydrolysis reaction was carried out at 80°C for 12 hours to obtain a TiO2 precipitate. After filtering and washing, the precipitate was dried at 100°C for 12 hours to obtain a TiO2 powder.
[0073] Step S4, composite of Cu-doped ZrTaON and TiO2: Cu-doped ZrTaON and TiO2 powders were mixed in a molar ratio of 1:0.5, ball-milled at 300 rpm for 6 hours to ensure uniform distribution, and then heat-treated at 400° C. for 3 hours to form a composite material of Cu-doped ZrTaON and TiO2.
[0074] Step S5: Cu-doped ZrTaON and TiO2 composite coating precursor Composite materials of Cu-doped ZrTaON and TiO2 and ternary precursor Ni 0.6 Co 0.2 Mn 0.2(OH)2 was mixed at a mass ratio of 0.03:1 and pretreated at 250°C for 4 hours to promote the bonding of the composite and the precursor. After sintering, the composite was cooled to room temperature to obtain a composite-coated precursor.
[0075] Step S6: Preparation of positive electrode material from the modified precursor The modified precursor and lithium hydroxide are reacted according to the precursor Ni 0.6 Co 0.2 Mn 0.2 (OH)2 and Li contained in lithium hydroxide are mixed in a molar ratio of 1:1.05, and sintered at 850°C in an air atmosphere for 22 hours to obtain a Cu-doped ZrTaON and TiO2 composite coated modified positive electrode material.
[0076] Example 5 Step S1, preparation of ZrTaON: first prepare 0.1 mol zirconium chloride (ZrCl4) and 0.1 mol potassium heptafluorotantalate (K2TaF7), dissolve them in 100 mL of 28 wt% ammonia water, and then heat to 60°C and stir to react. During the mixing process, nitrogen is introduced at a flow rate of 50 mL / min to ensure the protection of the reaction atmosphere and avoid oxidation. After the reaction, the precipitate is washed with deionized water 3 times to remove excess ions, filtered and dried, and the obtained dry product is sintered in a nitrogen atmosphere at 900°C for 4 hours to finally obtain ZrTaON powder.
[0077] Step S2, synthesis of Cu-doped ZrTaON: copper oxide (CuO) was added to the obtained ZrTaON powder, and the mixture was mixed at a molar ratio of ZrTaON to CuO of 100:5, and the mixture was sintered in a nitrogen atmosphere at 800° C. for 2 hours to uniformly dope the Cu element into the ZrTaON, thereby obtaining a Cu-doped ZrTaON composite material.
[0078] Step S3, preparation of TiO2: 10 mL of tetrabutyl titanate (Ti(OC4H9)4) was dissolved in 20 mL of isopropanol, followed by the addition of 50 mL of deionized water, and the pH was adjusted to 2 with 2M HNO3. The hydrolysis reaction was carried out at 80°C for 12 hours to obtain a TiO2 precipitate. After filtering and washing, the precipitate was dried at 100°C for 12 hours to obtain a TiO2 powder.
[0079] Step S4, composite of Cu-doped ZrTaON and TiO2: Cu-doped ZrTaON and TiO2 powders were mixed in a molar ratio of 1:0.2, ball-milled at 300 rpm for 6 hours to ensure uniform distribution, and then heat-treated at 450° C. for 2 hours to form a composite material of Cu-doped ZrTaON and TiO2.
[0080] Step S5: Cu-doped ZrTaON and TiO2 composite coating precursor Composite materials of Cu-doped ZrTaON and TiO2 and ternary precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 was mixed at a mass ratio of 0.05:1 and pretreated at 350°C for 3 hours to promote the bonding of the composite and the precursor. After sintering, the composite was cooled to room temperature to obtain a composite-coated precursor.
[0081] Step S6: Preparation of positive electrode material from the modified precursor The modified precursor and lithium hydroxide are reacted according to the precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and Li contained in lithium hydroxide are mixed in a molar ratio of 1:1.05, and sintered at 850°C in an air atmosphere for 22 hours to obtain a Cu-doped ZrTaON and TiO2 composite coated modified positive electrode material.
[0082] The positive electrode materials of Examples 1 to 5 and Comparative Examples 1 to 5 were respectively assembled into batteries in the following manner: the positive electrode material, the binder PVDF, and the conductive agent were mixed in a ratio of 8:1:1, and after dry grinding for 10 minutes, the solvent N-methyl-2-pyrrolidone (NMP) was added, and the positive electrode slurry was obtained after being stirred evenly with a homogenizer. The positive electrode slurry was evenly coated on an aluminum foil, dried in an oven at 90°C overnight to ensure that the coating was dry, and then cut into discs (12 mm in diameter) suitable for button batteries with a cutting machine; a metal lithium sheet was used as the negative electrode; the electrolyte LB-037 (1M LiPF6in DEC:EC:EMC=1:1:1 Vol%) was used as the electrolyte and 50uL was added dropwise, Celgard2325 was used as a separator, and assembled into a LIR2032 button battery.
[0083] The electrical performance of the battery was tested in the following manner: the test temperature was 25°C, the operating voltage range was 3.0~4.3V, 2 cycles were performed at 0.1C, and then 100 cycles were performed at 0.5C, 1C, and 2C.
[0084] The test results are shown in Table 1. It can be seen from Table 1 that the battery assembled with the modified positive electrode material prepared in Example 1 has a slightly lower discharge capacity than the battery assembled with the positive electrode material prepared in Comparative Example 5, and the cycle performance is significantly improved; the battery assembled with the modified positive electrode material prepared in Example 1 has a slightly lower discharge capacity than the battery assembled with the positive electrode material prepared in Comparative Example 1, but the cycle performance is significantly improved, indicating that the composite coating of Cu-doped ZrTaON and TiO2 is significantly improved in terms of the cycle stability of the positive electrode material in the battery compared to the single Cu-doped ZrTaON coating. In addition, the battery assembled with the modified positive electrode material prepared in Example 1 has not only an improved discharge capacity, but also significantly improved cycle performance compared to the battery assembled with the positive electrode material prepared in Comparative Examples 3 to 5. The battery assembled with the modified positive electrode material prepared in Comparative Example 1 has not only an improved discharge capacity, but also improved cycle performance compared to the battery assembled with the positive electrode material prepared in Comparative Example 2, because Cu-doped ZrTaON can effectively improve the conductivity of the material and enhance the structural stability.
[0085] It can also be seen from Table 1 that the batteries assembled from Examples 1 to 5 using the coated modified positive electrode materials with different Ni contents all have good electrical properties and cycle performance.
[0086] Table 1 The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A modified lithium battery precursor, characterized in that: It comprises a lithium battery precursor and a coating layer located on at least a part of the surface of the lithium battery precursor, wherein the lithium battery precursor is nickel cobalt manganese hydroxide, and the coating layer is a composite material of Cu-doped ZrTaON and TiO2.
2. The modified lithium battery precursor according to claim 1, characterized in that: The chemical formula of the nickel-cobalt-manganese hydroxide is Ni x Co y Mn z (OH)2, where 0.6≤x<1, 0≤y≤0.2, 0<z≤0.3, x+y+z=1; The mass ratio of the coating layer to the lithium battery precursor is 0.005-0.05:1; In the coating layer, the molar ratio of Cu-doped ZrTaON to TiO2 is 1:0.1-2, preferably 1:0.2-1.5; In the Cu-doped ZrTaON, the molar ratio of Cu to Zr is 0.005-0.1:
1.
3. The method for preparing a modified lithium battery precursor according to claim 1 or 2, characterized in that: include: S1. preparing Cu-doped ZrTaON material; S2, mixing Cu-doped ZrTaON and TiO2 and ball-milling to obtain a mixed powder, and heat-treating the mixed powder to obtain a composite material of Cu-doped ZrTaON and TiO2; S3, mixing nickel-cobalt-manganese hydroxide with the composite material, and then performing heat treatment to obtain a modified lithium battery precursor.
4. The method for preparing the modified lithium battery precursor according to claim 3, characterized in that: In step S1, the preparation of the Cu-doped ZrTaON material includes: preparing the ZrTaON material; mixing the ZrTaON material with a copper source, and calcining the mixture in a nitrogen atmosphere to obtain the Cu-doped ZrTaON material.
5. The method for preparing a modified lithium battery precursor according to claim 4, characterized in that: The copper source is one or more of copper oxide, copper sulfate, copper acetate, copper carbonate, and copper hydroxide; The calcination temperature is 600-1000° C. and the calcination time is 1-5 hours.
6. The method for preparing a modified lithium battery precursor according to claim 4, characterized in that: The preparation of the ZrTaON material comprises: dissolving zirconium chloride and potassium heptafluorotantalate in ammonia water according to a stoichiometric ratio, heating and reacting under a nitrogen atmosphere, washing, solid-liquid separation and drying the obtained precipitation product, and then sintering to obtain ZrTaON powder.
7. The method for preparing a modified lithium battery precursor according to claim 6, characterized in that: The temperature of the heating reaction is 50-80°C; The sintering temperature is 800-1000° C. and the sintering time is 3-5 hours.
8. The method for preparing a modified lithium battery precursor according to claim 3, characterized in that: In step S2, the temperature of the heat treatment is 200-500° C. and the time of the heat treatment is 1-6 hours; In step S3, the temperature of the heat treatment is 200-400° C.; the time of the heat treatment is 1-4 hours.
9. A positive electrode material, characterized in that The modified lithium battery precursor as claimed in claim 1 or 2 is mixed with a lithium source and then sintered to obtain the product.
10. A lithium ion battery, characterized in that Comprising the positive electrode material as claimed in claim 9.